Kinematic and muscle synergy patterns of the lower limbs during jump-landing with side-cutting in individuals with functional ankle instability - Ji, Xinqi; Li, Xiaoliang; Yu, Lijing; Song, Yongyue (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveThis study investigated lower-limb kinematics and neuromuscular control in individuals with functional ankle instability (FAI) during a standing long jump-landing side-cut tasks, and compared them with Copers (individuals with ankle sprain history but no persistent instability) and healthy controls to reveal synergy reorganization mechanisms underlying FAI and inform rehabilitation strategies.MethodsTen participants were included in each group (FAI, Coper, and control). For the jump-landing side-cut task, participants stood 80 cm behind a force plate, jumped forward maximally with both legs, landed on one test leg at the plate center, then immediately side-cut 30° to the opposite side of the test leg (lateral distance ≥80 cm from the plate). Lower-limb kinematics and electromyography were recorded during the task using a synchronized motion capture and EMG system. Muscle synergies were extracted via non-negative matrix factorization (NNMF, 90% variance accounted for as termination criterion) to compare synergy number, activation timing, and muscle contributions among groups.Results(1) The FAI group exhibited significantly greater knee and ankle flexion-extension and hip abduction angles compared with the Coper and control groups, while the Coper group showed a larger ankle range of motion than controls (p < 0.05). (2) All three groups demonstrated four common synergy modules. (3) The early synergy (Module 1) activation duration was shorter in the FAI and Coper groups than in controls, whereas the late synergy (Module 4) lasted longer in the FAI group (p < 0.05). (4) Significant differences in muscle weightings were observed among groups across modules (p < 0.05).ConclusionIndividuals with FAI adopt a protective movement strategy characterized by increased flexion and abduction to enhance stability. Muscle synergy analysis reveals an asymmetric activation pattern with reduced early activation, prolonged late compensation, and a proximal-dominant, delayed distal control pattern. Although the Coper group demonstrates movement characteristics more similar to healthy controls, mild over-flexion and delayed responses remain.